Landscape Biographies - Hermans, Rita; Kolen, Jan; Renes, Hans (Landscape and Heritage Research, 2014)
Landscape Biographies explores the long, complex histories of landscapes from personal and social perspectives. Twenty geographers, archaeologists, historians, and anthropologists investigate the diverse ways in which landscapes and monuments have been constructed, transmitted, and transformed from prehistory to the present, from Manhattan to Shanghai, Iceland to Portugal, England to Estonia.